8.14 MODERNIST TRENDS IN DAZAI OSAMU’S NOVEL THE SETTING SUN - Mamurjonova G.R. (teacher) Tursunova N.T. (senior teacher) at the Department of Japanese philology TSUOS (Innovative technologies in construction Scientific Journal, 2024)
This article examines the modernist trends in the novel "The Setting Sun" by the Japanese modernist writer Dazai Osamu. Dazai Osamu is one of the greatest writers of the 20th century. His work cannot be attributed to any particular genre. Many call him a classic of the "novel about himself" ("watakushi-sesetsu"), others talk about his proximity to romanticism, but despite the fact that both are undoubtedly present in his work, it is difficult to fit Osamu Dazai’s prose into the narrow framework of one genre. The Setting Sun is one of Dazai Osamu’s novels. Here the author shows the decline of an aristocratic family in the first post-war years, expressing fear of the impending storm and warning that the revolution is hostile to beauty and humanity. Keywords: The twentieth century, the novel "The Setting Sun", "existentialism", Dazai Osamu, "The Cherry Orchard", Meiji, Japan, the war, "a novel about myself" ("watakushi-sesetsu"). The beginning of the twentieth century in many countries was marked by tragic political upheavals, the development of society in all 245 spheres of its life, and so rapid that many could not adapt to the changes in any way, so that gradually the entire world community lost morale. Japan embarked on a particularly active development path with the onset of the Meiji Restoration in the second half of the nineteenth century and by the first decade of the twentieth century had become an influential state at the stage of transition from the feudal system to the capitalist one. Feudal traditions have been developing in Japan for many centuries, and their almost instantaneous destruction was followed by the collapse of the people’s faith in the bright future of the country. The Japanese had no idea what to expect from the next day: political parties arose one after another, workers and students did not stop striking, part of society fought to preserve the feudal system, some advocated the ideals of Marxism, but there were always those who were simply tired of wars and coups. At this difficult time, on June 19, 1909, in the city of Kanagi, Aomori Prefecture, Dazai Osamu was born, who entered the history of Japanese literature as one of its most tragic figures. The real name of the writer – Tsushima Shuji is one of the greatest writers of the 20th century. His work cannot be attributed to any particular genre. Many call him a classic of the "novel about himself" ("watakushi-sesetsu"), others talk about his proximity to romanticism, but despite the fact that both are undoubtedly present in his work, it is difficult to fit Osamu Dazai’s prose into the narrow framework of one genre [1-9].